The Effectiveness of Fraction Blocks Media on Mathematics Learning Outcomes in the Topic of Fractions - Ida Purnama Sari; Mardiyana Mardiyana; Supianto Supianto (Journal of Educational Sciences, 2026)
Teaching mathematics on the topic of fractions remains a challenge for elementary school students because the concepts are abstract. This study aims to determine which learning medium fraction blocks or video yields higher mathematics learning outcomes on the topic of fractions. The study employed a quantitative approach using a quasi-experimental method and a non-equivalent comparison group design. The sample consisted of 60 students selected through cluster random sampling. The sample consisted of sixth-grade students from Diponegoro Elementary School Cluster in Eromoko Subdistrict, divided into an experimental group and a control group. The experimental group used fraction blocks, while the control group used video. Data were collected using a learning achievement test consisting of 20 multiple-choice questions that met validity and reliability criteria. Data analysis involved tests of normality, homogeneity, balance, and an independent samples t-test. The results of the study indicate that there is a difference in students’ mathematics learning outcomes between the group using fraction blocks and the group using video (p = 0.0145 < 0.05). The average learning outcomes of students using fraction blocks were higher than those of students using video. Thus, fraction blocks are effective for improving students’ mathematics learning outcomes on the topic of fractions.